Minimising pain and medical adhesive related skin injuries in vulnerable patients. (8th August 2019) - Collier, Mark
Abstract : The skin is the largest and one of the most important organs of the body and as such it is essential that skin integrity is maintained to preserve normal body functions as much as possible at all times. Health professionals must endeavour to minimise any pain and trauma likely to be encountered by their patients through the use of a variety of medical products and devices that are designed to adhere to the skin, especially as the use of dermatological and wound-management products in particular, that incorporate adhesives to help keep them secure and in place, has grown in line with the increasingly ageing population and changing demographics throughout the UK. This article reviews the literature related to the causes of medical-adhesive-related skin injuries (MARSIs) and the reported patient effects, in particular pain and skin trauma and highlight some 'at-risk' patient groups and potential actions to minimise risk. A sterile silicone medical adhesive remover—Appeel Sterile—is introduced and the clinical benefits highlighted through the discussion of clinical evidence and case studies undertaken on a range of patients with varied aetiologies.